2019
DOI: 10.1038/s41598-019-42449-7
|View full text |Cite
|
Sign up to set email alerts
|

Early and Pre-Clinical Detection of Prion Seeding Activity in Cerebrospinal Fluid of Goats using Real-Time Quaking-Induced Conversion Assay

Abstract: Since 2005, two cases of natural bovine spongiform encephalopathies (BSE) have been reported in goats. Furthermore, experimental transmissions of classical (C-BSE) and atypical (L-BSE) forms of BSE in goats were also reported. To minimize further spreading of prion diseases in small ruminants the development of a highly sensitive and specific test for ante-mortem detection of infected animals would be of great value. Recent studies reported high diagnostic value of a second generation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…We investigated the performance of the three assay platforms at 55°C because the amplification reaction accelerates at higher temperatures [1619]. We compared brain homogenates infected with CWD, sCJD and vCJD, three naturally occurring infections, tested with QuIC-C and RT-QuIC using truncated recombinant substrates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the performance of the three assay platforms at 55°C because the amplification reaction accelerates at higher temperatures [1619]. We compared brain homogenates infected with CWD, sCJD and vCJD, three naturally occurring infections, tested with QuIC-C and RT-QuIC using truncated recombinant substrates.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, assaying biological materials containing minute amounts of PrP TSE by RT-QuIC can take 40–50 hours or longer [1315]. Recent modifications of the method conducting the reaction at 55°C and using truncated prion protein as the substrate, have markedly reduced lag times [1619]. However, RT-QuIC assay time is a function of PrP TSE concentration in the test materials, requiring longer times to detect low levels of the abnormal protein.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, although atypical scrapie could be detected in brain tissue [42], no report has been found on atypical scrapie detection in CSF. An improved version of RT-QuIC, also known as second generation RT-QuIC, has been similarly applied to CSF from classical BSE and L-BSE infected goat, in which PrP Sc was detected in preclinical and clinical stage [88]. Finally, it is worth mentioning the detection of Chronic Wasting Disease (CWD) prions in CSF of affected cervids, for which both PMCA and RT-QuIC have been used.…”
Section: Prp Sc In Csf In Animal Prion Diseasesmentioning
confidence: 99%
“…Experimental transmission by the intracerebral route to sheep and goats showed that both species are susceptible to L-BSE with an efficiency of infection as high as 100% and preferential accumulation of PrP sc in the central nervous system (CNS) and to a lesser extent in the peripheral nervous system, in the cerebrospinal fluid and in the lymphoreticular system (LRS) [ 1 – 5 ].…”
Section: Introductionmentioning
confidence: 99%